CSR DAN MASYARAKAT: STUDI MODEL IMPLEMENTASI CSR DI ACEH TAMIANG DAN IMPLIKASINYA TERHADAP MAQASHID SYARIAH - Abdullah AR, Muhammad Dayyan dan (IAIN Langsa, 2016)
Abstrak.This article analysed the implementation model of the Coorporate Social Responsibility (CSR) in Kabupaten Aceh Tamiang by qualitative approach. After conducting field survey and interview with company staff in charge, public figure, and governmental officer in change, it was found that the company that involved in Palm Oil Tree Plantation, and the Crude Palm Oil Industries (CPO), they only implement the CSR in the form of philantrophic program as a response to the need for establishing good relationship with the local people. On the PT. Pertamina which involved in oil and gas exploration that had designed and developed a well plan CSR program. It provided support for community economic empowerment, environmental rehabilation, and infrustruture development. In term of the implication on the maqashid syariah for the protection of religion, life, mind, family or progeny and the propertis is still lower than the expection. The local community felt indifferent and dissatisfied with regard to benefit they recieved from the company, comparing to the surplus return that company gained out of natural exploitation. The welfare of the local people and future generation and the distruction of nature, that would affect the life and health of the people, all these had not well addressed by the CSR program of those companies. Kata Kunci: Implementasi CSR, implikasi maqashid syariah, dan perusahaan